Iodine Levels in Pregnant Women with Hyperemesis Gravidarum - Seyma Banu Arslanca; Vakkas korkmaz; Tufan Arslanca; Figen Besyaprak; Adil Barut (Gynecology Obstetrics & Reproductive Medicine)
Objective: Iodine deficiency is a commonly seen problem and associated with pregnancy complications. In this study, we aimed to evaluate urinary iodine status in pregnant women with hyperemesis gravidarum